2017
DOI: 10.1002/jeab.264
|View full text |Cite
|
Sign up to set email alerts
|

Aversive functions of response effort: Fact or artifact?

Abstract: Historically, effort has been viewed as aversive. Most supporting evidence comes from studies demonstrating increased force/effort requirements reduce operant responding. Changes in force/effort requirements, however, are often accompanied by changes in response definition when mechanical devices are used to define the response. As a consequence, responses measured at one point in a study may go unmeasured at other points. In an alternative approach, we used a continuous measurement strategy that provided a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
(51 reference statements)
0
12
0
1
Order By: Relevance
“…However, we also observed unreinforced responses that produced longer latencies to the target behavior (see bottom panel of Figure ). Responses that fall above the threshold but below criterion have been referred to as subcriterion responses (Pinkston & Libman, ). The implication for applied work is that rates of target behaviors may often be an artifact of the criterion.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also observed unreinforced responses that produced longer latencies to the target behavior (see bottom panel of Figure ). Responses that fall above the threshold but below criterion have been referred to as subcriterion responses (Pinkston & Libman, ). The implication for applied work is that rates of target behaviors may often be an artifact of the criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Bands limits were informed by our previous work on force. We have found that responding can be maintained within the range of 5 – 80 g. Increasing the force beyond that range results in unreliable responding and forces in excess of 100 g has eliminated responding in every rat we have studied (e.g., Pinkston & Libman, ). Thus, the span of the bands cover the range of forces where responding can be sustained reliably.…”
Section: Methodsmentioning
confidence: 86%
“…Recently, our lab examined force distributions maintained by fixed‐ratio schedules (Pinkston & Libman, ). An analysis of the distributions showed relatively consistent coefficients of variation as force requirements increased, indicating force production obeys Weber's Law.…”
Section: Resultsmentioning
confidence: 99%
“…Although basic research has suggested that participants generally prefer low effort to high effort conditions (Perone & Baron, 1980), and that increased effort requirements generally reduce responding (Chung, 1965), more recent data suggest that increased effort may not be as aversive as previously thought. Pinkston and Libman (2017) note that most basic research on effort has employed levers with minimum response forces. For example, a lever with a minimum force of 20 g can only be depressed when at least 20 g of force is applied.…”
Section: Discussionmentioning
confidence: 99%